Expansion of a multi-pronged safe sleep quality improvement initiative to three children's hospital campuses - Traci Leong; Kerryn Roome; Terri Miller; Olivia Gorbatkin; Lori Singleton; Maneesha Agarwal; Sarah Gard Lazarus (BMC, 2020)
Abstract Background The American Academy of Pediatrics (AAP) recommends infants should be Alone, on their Back, and in a clear Crib to combat relatively stagnant rates of sudden unexpected infant death (SUID). These are referred to as the ABCs of safe sleep. Studies have shown these recommendations are not consistently followed in the hospital setting, but further investigation would determine how to improve the rate of adherence. The objective of this study was to evaluate the impact of an expanded safe sleep initiative at three Georgia free-standing children's hospital campuses before and after a multipronged safe sleep initiative. Methods A quality improvement program with a pre/post analysis was performed using a convenience method of sampling. Infants < 12 months old in three inpatient pediatric campuses were analyzed pre- and post- interventions. The intervention included: 1) nursing education, 2) identification of nurse "safe sleep" champions, 3) crib cards, 4) crib audits, and 5) weekly reporting of data showing nursing unit ABC compliance via tracking boards. The goal was ABC compliance of ≥25% for the post-intervention period. A standardized crib audit tool evaluated sleep position/location, sleep environment, and ABC compliance (both safe position/location and environment). Chi square analysis, Fisher's exact test, and logistic regression were used to compare safe sleep behaviors before and after the interventions. Results There were 204 cribs included pre-intervention and 274 cribs post-intervention. Overall, there was not a significant change in sleep position/location (78.4 to 76.6%, p = 0.64). There was a significant increase in the percent of infants sleeping in a safe sleep environment following the intervention (5.9 to 39.8%, p < 0.01). Overall ABC compliance, including both sleep position/location and environment, improved from 4.4% pre-intervention to 32.5% post-intervention (p < 0.01). There was no significant variability between the hospitals (p = 0.71, p = 1.00). Conclusions The AAP's safe sleep recommendations are currently not upheld in children's hospitals, but safer sleep was achieved across three children's campuses in this study. Significant improvements were made in sleep environment and overall safe sleep compliance with this multi-pronged initiative.